The effect of society participation, budget, and organization on the effectiveness of pond maintenance program in Kobalima District, Malaka Regency - Herlyani Seran; Nursalam Nursalam; Lenny M. Tamunu (Goodwood Publishing, 2022)
Purpose: The discussion of this research is Society Participation, Budget, and Organization on the Effectiveness of Pond Maintenance Program in Kobalima District, Malaka Regency. Research Methodology: This study uses quantitative research methods with sampling techniques in research using the Slovin formula and data analysis techniques using regression, namely looking for the effect of each independent variable on the dependent variable, and the instrument used in this study is intended to produce accurate data by using a Likert scale. Results: Each independent variable, namely society participation, budget, and organization, partially has a significant influence on the effectiveness of the pond maintenance program. Simultaneous society participation, budget, and organization also have a significant effect on the effectiveness of the pond maintenance program. Limitations: Research variables are complex and research results may change in the future. Contribution: Research findings can serve as a basis for evaluation and the basis for maintaining existing good performance in promoting an effective pond maintenance program.